A Field-Based Experiment on the Influence of Stand Density Reduction on Watershed Processes at the Caspar Creek Experimental Watersheds in Northern California - Dymond, Salli F.; Richardson, Paul W.; Webb, Lynn A.; Keppeler, Elizabeth T.; Arismendi, Ivan; Bladon, Kevin D.; Cafferata, Peter H.; Dahlke, Helen E.; Longstreth, David L.; Brand, Patrick K.; Ode, Peter R.; Surfleet, Christopher G.; et al. (Frontiers in Forests and Global Change, 2021)
Forests are integral to sustaining clean water resources and healthy watersheds. It is critical, therefore, that managers fully understand the potential impacts of their actions on myriad ecosystem services provided by forested watersheds. While forest hydrologists have long used paired-watershed experiments to elucidate the complex interactions between forest management and watershed biogeochemical and ecohydrological processes, there is still much to learn from these studies. Here, we present an overview of the process for designing a paired-watershed study using a large harvesting experiment at the Caspar Creek Experimental Watersheds in coastal California as an example. We detail many considerations when designing such an experiment and highlight the wide range of scientific investigations that are part of the larger experiment. Paired watershed studies are a great example of community engaged scholarship and offer the unique opportunity to work with land managers to solve applied problems while simultaneously discovering new fundamental knowledge about how watersheds function.